Challenges of breast cancer screening in transgender (Research, Society and Development, 2021)
Objective: To analyze evidence from the literature on the challenges of breast cancer screening in transgender men and women. Methodology: Integrative review study, carried out in the following databases: Latin American and Caribbean Literature on Health Sciences (LILACS), Medical Literature Analysis and Retrieval System Online (MEDLINE), Virtual Health Library (VHL), Scientific Electronic Library Online (SciELO) and the United States National Library of Medicine (PUBMED). Results: The sample consisted of eleven articles. It was identified that the challenges of breast cancer screening in transgender people are associated with variables such as: low financial condition, disabled professional to serve the transgender public, absence of a specific guideline for screening and health services with discriminatory practices. Conclusion: Therefore, it is necessary to understand the aforementioned cancer epidemiology and the specific needs for prevention and treatment in transgender populations, which also adopt public policies to reduce stigma and discrimination related to gender diversity.